Toward an understanding of recent developments in RPL routing. Issue 6 (1st November 2019) - Alsukayti, Ibrahim S.; Alreshoodi, Mohammed
Abstract : The ability to enhance network routing for flexible support of different application requirements is essential to widen the horizon for the Internet of things (IoT) deployments. The Internet protocol (IP) version 6 routing protocol for low‐power and lossy networks (RPL) provides an effective routing solution addressing such a challenge. It realises flexible end‐to‐end IP routing that can be adapted to support different IoT applications. This is based on the concept of customisable objective functions (OFs), which facilitates application‐specific routing using a wide range of routing metrics. There are only two default OFs of basic routing metrics, which are specified by the Internet engineering task force for RPL. However, a number of others have been proposed by the network research community to address single‐ and multi‐objective RPL routing enhancement. These research proposals followed different methodological approaches and adopted a variety of routing metrics to achieve different optimisation goals. Up‐to‐date research efforts to improve RPL routing and topology optimisation have been reviewed, and recent RPL OFs and routing metrics in the literature have been discussed. The major aim is shedding light on relevant contributions to establish a firm understanding of recent RPL developments and outline plausible areas for follow‐up researches.